A Tale of Two Cities: Understanding Differences in Levels of Heroin/Crack Market-Related Violence—A Two City Comparison. (March 2015) - Coomber, Ross
Despite increasing evidence of greatly differentiated illicit drug markets, common depictions and conceptualizations of "the" drug market remain subject to overhomogenization. As regards drug market-related violence, the conceptualization of drug supply milieu as generally violent has often (sometimes unintentionally) been apparently supported by case study research reporting from particularly violent supply milieu and/or on specific groups of suppliers. Little research has focused on the relative absence of violence in supply milieu. Although some prior research has pointed toward ways in which levels of drug market violence can differ, few examples have shown this empirically by reference to comparative case studies and none have attempted to relate this to differentiation as opposed to market emergence, maturity, and decline. This article reports on two case studies of established heroin/crack markets in two separate coastal cities in England that share many characteristics but differ meaningfully in regard to drug market violence. Meaningful historical and extant differences in supply-related violence is reported and reflected upon and it is concluded that drug-related violence, rather than conforming to conventional notions privileging structural or systemic similarity, is contingent on a mix of local supply cultures, supplier rationality, local supply structures as well as supplier characteristics and that each and any supply locale is likely, if studied closely, to differ in meaningful respects across time and practice to another.